Characterizations of rice husk based silica made from acid leaching extraction method - Muralli Arivalan; Hoe Kwan Wai; Aun Abbas Muhammad; Hasnolhadi Samsudin Muhammad (E3S Web of Conferences)
Rice husk is a material that is greatly acquired through agriculture, which opens up as a source for silica. It available in high quantity that has potential to be used in the concrete. Consequently, this research aims to address this gap by extracting and characterizing the silica from rice husks using the acid leaching method. The different leaching duration of for 6, 12, 18, and 24 hours is the main point of focus in this research. Leaching was done using 0.1 M HCl at room temperature. The XRD, EDX, and SEM are used to characterize the silica. The outcome has been achieved for leaching a period of 24 hour at room temperature was optimal for producing amorphous silica with minimal crystalline and smoothest surface morphology. The study explores an energy efficient and mass production method for silica extraction from rice husks.